Determinants of financial attitudes among secondary-school students in Singapore - Keng, K.N.; Fraser, Barry (James Nicholas Publishers, Pty. Ltd., 2014)
We investigated instructional, sex and school-level determinants of students' financial attitudes among 4801 students in 25 secondary schools in Singapore. A two-scale financial attitudes questionnaire was developed to assess students' attitudes to financial management and attitudes to financial literacy programs. Data analyses revealed that the attitude questionnaire was valid and reliable when used with these Singaporean school students. A three-way MANOVA for instructional, sex and school-level differences in student attitudes revealed that: students who attended financial literacy programs had significantly more positive attitudes on both scales; females had significantly more positive attitudes to financial literacy programs than did males; and upper-secondary students had more positive attitudes to financial literacy programs than did lower-secondary students.